2021
DOI: 10.3390/plants10061074
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Cowpea (Vigna unguiculata) Yield and Control Insecticide Exposure in a Semi-Arid Region

Abstract: The aim of this study was to evaluate the adaptability of different genotypes of cowpea (Vigna unguiculata L. Walp.) in the edaphoclimatic conditions of a semi-arid region. In the experimental design, a completely randomized split-plot (2 × 8), with 3 repetitions (blocks) was used. The experiment comprised 7 new genotypes and 1 local genotype as the first main factor and application of insecticide as a secondary factor. Two-factor analysis of variance (two-way ANOVA) determined the differences between the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…In fact, this crop shows relatively high adaptation to drought, especially in comparison to other legumes [57] and can fix up to 200 kg N ha −1 [58] with a positive soil N balance of up to 92 kg ha −1 [59]. Nevertheless, several abiotic and biotic constraints (i.e., low soil fertility, pests, diseases, parasitic weeds, and nematodes) limit the yield [43,60,61]. Moreover, low productivity is often associated with the use of traditional and unimproved varieties, still widely cultivated in Africa [62].…”
Section: Vigna Unguiculata (L) Walpmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, this crop shows relatively high adaptation to drought, especially in comparison to other legumes [57] and can fix up to 200 kg N ha −1 [58] with a positive soil N balance of up to 92 kg ha −1 [59]. Nevertheless, several abiotic and biotic constraints (i.e., low soil fertility, pests, diseases, parasitic weeds, and nematodes) limit the yield [43,60,61]. Moreover, low productivity is often associated with the use of traditional and unimproved varieties, still widely cultivated in Africa [62].…”
Section: Vigna Unguiculata (L) Walpmentioning
confidence: 99%
“…Thanks to this residual genetic diversity and also to studies performed on Vigna species, most of the accessions are well adapted to a wide range of extreme environmental conditions, such as sandy beaches, arid lands and wetlands, harbouring tolerance and resistance genes towards biotic and abiotic stresses. These genetic traits are used for developing new stress-tolerant crops [37][38][39][40][41][42][43]. By contrast, less is known about the effects of domestication on the nutritional value of seeds [7] even if recent studies have reported that cultivated legumes show a lower carotenoid and protein content in seeds compared with the wild relatives [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Vast literature documented on its importance and production, indicate that grain yield estimates are still far below estimates to meet growing population demands (Horn et al, 2017). Several findings have implicated the unavailability of seeds of improved cultivars, unfavourable climatic conditions, diseases, insect pests and parasitic weeds, as major causes of the low production and productivity observed in grain cowpea (Boukar et al, 2018;Carvalho and Halecki, 2021). Horn et al (2017) reported grain yield ranging from 0.10 to 0.60 tha -1 which were far below potentially attainable yields of 1.5 to 3.0 tha -1 .…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Its high protein content (25%, dry weight basis) is key in alleviating malnutrition and poverty, especially in Sub-Saharan Africa (SSA). In particular, in Portuguese-speaking African countries (PALOP) such as Angola, cowpea is an important staple crop [ 3 ], and in Mozambique, it is, at present, the most cultivated legume [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%